2019
DOI: 10.1016/j.nmni.2019.100595
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Orientia tsutsugamushi causing scrub typhus among febrile patients in north-central Bangladesh

Abstract: Scrub typhus is a mite-borne rickettsial disease caused by Orientia tsutsugamushi, which is endemic in Asia Pacific region. In this study, infection rate and molecular epidemiologic traits of O. tsutsugamushi was investigated in Mymensingh, located in north-central Bangladesh. Among the blood samples from 453 febrile patients who visited Mymensingh medical college hospital in 2018, the 47 kDa protein gene of O. tsutsugamushi was detected in 78 samples (17.2%) by nested PCR. Phylogenetic analysis of the O. tsut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…The Karp-related strains were the predominant genotype observed in Southeast Asia (Thailand, Vietnam, Cambodia and Taiwan), East Asia (Japan, China), Northeast India and Bangladesh. 7,[23][24][25] A study from eastern region of India reported the occurrence of Kato as the single most prevalent strain. 19 In a study from North India, Gilliam has been identified to be the most common genotype, followed by Karp-like strains.…”
Section: Discussionmentioning
confidence: 99%
“…The Karp-related strains were the predominant genotype observed in Southeast Asia (Thailand, Vietnam, Cambodia and Taiwan), East Asia (Japan, China), Northeast India and Bangladesh. 7,[23][24][25] A study from eastern region of India reported the occurrence of Kato as the single most prevalent strain. 19 In a study from North India, Gilliam has been identified to be the most common genotype, followed by Karp-like strains.…”
Section: Discussionmentioning
confidence: 99%